Facilitation, Interference, or Both? Disentangling Processes in the Stroop, Simon, and Flanker Tasks Using Neutral Conditions and Distributional Analyses. - Croizet, Pablo; Belletier, Clément; Jobert, Clotilde; Nahed, Yasmine; Ferrand, Ludovic (Journal of Experimental Psychology. Human Perception & Performance, 2026)
Inhibition is crucial to adapt to new situations and resist distraction, making it a central focus of research. Here, we compare three tasks considered as gold standards for measuring inhibition: the Stroop, Simon, and Flanker tasks. These tasks involve one relevant and one irrelevant dimension. In congruent trials, both dimensions activate the same response, whereas they activate opposing ones in incongruent trials. Global interference, the reaction time difference between these trial types, confounds both the facilitation and interference effect from the task-irrelevant dimension. To better understand the underlying processes at play within these tasks, we introduced neutral trials. Distributional analyses examined the impact of reaction time on mere interference (incongruent − neutral) and mere facilitation (congruent − neutral). Our findings, replicated in Experiment 2, challenge established theories by suggesting that the classic negative-going Simon delta plot reflects a transient and automatic facilitation process, rather than slow-building inhibition. Moreover, we show that the Stroop, Simon, and Flanker tasks differ systematically in how mere interference and mere facilitation shape global interference, while also warning against misinterpreting automatic processes as controlled processes in accounts of conflict resolution. Public Significance Statement: In daily life, we often rely on automated behaviors to efficiently navigate familiar tasks. However, novel or complex situations require cognitive control, the ability to regulate thoughts and actions to achieve specific goals. This study focuses on one key aspect of cognitive control: inhibition, our ability to suppress impulsive responses and distracting information. Inhibition is classically measured through conflict tasks, such as the Stroop, Simon, and Flanker tasks. In this work, we show that performance in these tasks may rely on automatic processes to the same extent as on controlled processes, such as inhibition. In some tasks, automatic processes may even play a stronger role, which directly challenges established theoretical frameworks.